Telemedicine portal - Islam, Md. Tauhidul; Oishee, Mayesha Samiha; Toma, Sabira Roshid; Khan, Mashrur Ahmed (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.